2020
DOI: 10.1200/jco.2020.38.6_suppl.10
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance or metastasis-directed therapy for oligometastatic prostate cancer recurrence (STOMP): Five-year results of a randomized phase II trial.

Abstract: 10 Background: Multiple randomized phase II trials suggest that metastasis-directed therapy (MDT) for oligometastatic prostate cancer (PCa) improves progression-free survival, but the majority of trials lack longer follow-up. We present the updated 5-year results from the STOMP-trial. Methods: In this multicentre, randomised, phase II study, asymptomatic PCa patients were eligible in case of a biochemical recurrence following primary PCa treatment with curative intent and presenting with up to 3 extracranial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 0 publications
1
57
0
3
Order By: Relevance
“…With a median follow-up of 3 years, mCRPC-free survival was almost 90% in both groups which is similar to our findings (93% at 3 years follow-up). In addition, an update of the STOMP trial showed that the 5-year mCRPC free survival was 76% in the MDT group which is also similar to our results (82% at five years) [ 24 ]. Suardi et al reported long-term outcomes of 59 oligorecurrent PCa patients treated by sLND with a median follow-up of more than 6 years [ 9 ].…”
Section: Discussionsupporting
confidence: 88%
“…With a median follow-up of 3 years, mCRPC-free survival was almost 90% in both groups which is similar to our findings (93% at 3 years follow-up). In addition, an update of the STOMP trial showed that the 5-year mCRPC free survival was 76% in the MDT group which is also similar to our results (82% at five years) [ 24 ]. Suardi et al reported long-term outcomes of 59 oligorecurrent PCa patients treated by sLND with a median follow-up of more than 6 years [ 9 ].…”
Section: Discussionsupporting
confidence: 88%
“…Progression at 6 months occurred in 61% of the patients in the observation arm but only 19% in the treated group. With increased follow-up of the STOMP trial, data is emerging that patients treated with MDT may experience increased time to castrate resistance ( 54 ). Criticisms of these trials include the lack of control arm of immediate ADT and the use of the surrogate end point ADT-free survival, however, for older men, with limited life expectancy this remains a clinically meaningful endpoint.…”
Section: Focal or Involved Node Stereotactic Body Radiation Therapymentioning
confidence: 99%
“…We hypothesize that involved field SBRT will decrease tumor burden in lymph nodes and delay transition to bone metastases and castration resistance ( 54 ). However, if involved field SBRT to oligo-recurrent nodal disease causes a significant rate of high-grade late toxicity and/or adversely affected patients' long-term quality of life this approach would not be worth pursuing further.…”
Section: Proposed Dose Constraintsmentioning
confidence: 99%
“…The most studied treatment approach in patients with oligometastatic recurrent PCa, is metastasis-directed local therapy (MDT; for example, stereotactic radiotherapy or surgery), with the potential goals of delaying the start of ADT and influencing prognosis [ 56 ]. A recent randomized phase II study of patients with oligometastatic recurrent PCa showed improved ADT-free survival in patients who underwent MDT compared to surveillance [ 57 ]. The effect of MDT on OS needs to be addressed in further clinical trials.…”
Section: Modern Nuclear Imaging In Prostate Cancer: New Pet/ct Radmentioning
confidence: 99%